2012
DOI: 10.2106/jbjs.k.00748
|View full text |Cite
|
Sign up to set email alerts
|

How to Treat Osteochondritis Dissecans of the Knee: Surgical Techniques and New Trends

Abstract: All of the techniques were effective in achieving good clinical and radiographic results in patients with osteochondritis dissecans, and the effectiveness of autologous chondrocyte implantation was confirmed at a mean follow-up of five years. Newer techniques such as MaioRegen implantation and the "one-step" transplantation technique are based on different rationales; the first relies on the characteristics of the scaffold and the second on the regenerative potential of mesenchymal cells. Both of these newer p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
57
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(63 citation statements)
references
References 22 publications
5
57
0
1
Order By: Relevance
“…Kon et al [21] showed that multilayer collagen/nanohydroxyapatite scaffolds promoted bone and cartilage tissue restoration. Nevertheless, improvement in the mechanical properties/stability of bilayered scaffold and optimization of the incorporation of bioactive factors in the scaffolds are still big challenges [17,24,25]. Other problems are related to achieving a good interface between the different layers [26].…”
Section: Introductionmentioning
confidence: 99%
“…Kon et al [21] showed that multilayer collagen/nanohydroxyapatite scaffolds promoted bone and cartilage tissue restoration. Nevertheless, improvement in the mechanical properties/stability of bilayered scaffold and optimization of the incorporation of bioactive factors in the scaffolds are still big challenges [17,24,25]. Other problems are related to achieving a good interface between the different layers [26].…”
Section: Introductionmentioning
confidence: 99%
“…Porous bone scaffolds promote the bone growth and can serve as carrier for drugs and stem cells (Ma et al, 2015;Mravic, Peault, & James, 2014). In addition to the application for structural bone restoration, multilayered scaffolds could also be used to support the tissue healing in case of chondral and osteochondral defects, for example, of knee lesions (Delcogliano et al, 2014;Kon et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…A review by Kon et al 12 summarised different effective surgical techniques to manage femoral condyle OCD. They discussed massive osteochondral autologous transplantation that involves shaping up the defect and press-fitting a squared contoured graft into the recipient bed.…”
Section: Discussionmentioning
confidence: 99%